2022
DOI: 10.1111/hiv.13425
|View full text |Cite
|
Sign up to set email alerts
|

Late diagnosis of HIV: An updated consensus definition

Abstract: Introduction: In recent years, HIV testing frequency has increased, resulting in more people being diagnosed during seroconversion with a temporarily low CD4 count. Using the current consensus definition of late HIV presentation ('presenting for care with a CD4 count < 350 cells/μL or an AIDS-defining event, regardless of CD4 count') these individuals would be incorrectly assigned as being diagnosed late. Methods: In spring 2022, a European expert group convened to revise the current late HIV presentation cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…Late HIV diagnosis is defined as a CD4 count below 350 cells/mm³ of blood within 91 days of diagnosis, excluding individuals with evidence of recent HIV acquisition (either a negative test in the 24 months before their first positive HIV test, or the result of a Recent Infection Testing Algorithm). 10,11 and health-seeking behaviour (including reduced access to sexual health services) may have contributed to the increase in the proportion of late HIV diagnoses seen in 2020 and 2021. 10 Mortality also increased markedly during the COVID-19 pandemic, underlining the consequences of late diagnosis.…”
Section: Hiv Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Late HIV diagnosis is defined as a CD4 count below 350 cells/mm³ of blood within 91 days of diagnosis, excluding individuals with evidence of recent HIV acquisition (either a negative test in the 24 months before their first positive HIV test, or the result of a Recent Infection Testing Algorithm). 10,11 and health-seeking behaviour (including reduced access to sexual health services) may have contributed to the increase in the proportion of late HIV diagnoses seen in 2020 and 2021. 10 Mortality also increased markedly during the COVID-19 pandemic, underlining the consequences of late diagnosis.…”
Section: Hiv Diagnosismentioning
confidence: 99%
“…9
Definition of late HIV diagnosis.Late HIV diagnosis is defined as a CD4 count below 350 cells/mm³ of blood within 91 days of diagnosis, excluding individuals with evidence of recent HIV acquisition (either a negative test in the 24 months before their first positive HIV test, or the result of a Recent Infection Testing Algorithm). 10,11
…”
Section: Introductionmentioning
confidence: 99%
“…43 In the current Recently, it has been suggested that the current casesurveillance definition of late diagnosis has the potential to overestimate "late diagnosis" due to low CD4 levels at the time of seroconversion, especially in frequently tested patient groups, and various suggestions have been made to overcome this issue. [62][63][64] This study was conducted by taking into account the existing consensus definitions.…”
Section: Factors Associated With Late Presentation and Late Presentat...mentioning
confidence: 99%
“…Late diagnosis of HIV and viral hepatitis continues to be a problem across Europe and beyond. An estimated one in five people living with HIV do not know their status, and half are diagnosed late in the World Health Organization (WHO) European region [1][2][3][4]. An estimated 80% of people with hepatitis B virus (HBV) infection and 73% of those with hepatitis C virus (HCV) infection are unaware of their infection in the European Union (EU)/European Economic area (EEA) [5].…”
Section: Introductionmentioning
confidence: 99%